Transmission performance of implicit optical label switching system with coherently detected spectral amplitude code labels - 张家洪 曹永盛 陈福深 李城鑫 (Optoelectronics letters, 2013)
A new optical label switching system with coherently detected implicit spectral amplitude code （SAC） labels is proposed in this paper. The implicit SAC labels are recognized using a frequency-swept local light source oscillator. An explicit SAC-label switching system with 40 Gbit/s intensity modulation （IM） payloads and 156 Mbit/s label and an implicit SAC-label switching system with 2.5 Gbit/s IM payloads and 156 Mbit/s label are both considered. Label and payload bit error rate （BER） performance is assessed and compared by simulations. The results reveal that after 80 km transmission and at the BER of 10＂9, the received optical power （ROP） values of label and payload are -8.3 dBm and -23.5 dBm in implicit SAC-label switching system, respectively, while those are -18.2 dBm and -18.6 dBm in explicit SAC-label switching system, respectively. As a result, the payloads of 40 Gbit/s and 2.5 Gbit/s in explicit/implicit SAC-label switching system have little influence on the received payload quality at the BER of 10-9 after 80 km transmission. Finally, a payload of 40 Gbiffs can obtain 12.5 dB optical signal-to-noise ratio （OSNR） after 80 km transmission.